After COP27 what next for SIDS and NbS? - Chan Soo, Rhonda (Instituto Interamericano de Ciencias Agrícolas (IICA), 2023)
Identify some questions with to Dr. Chaney St. Martin, where the answers focus on the current state of climate change and how to take the issue through COP27